LEGALIZATION OF CRIMINAL PROFIT IN THE COURSE OF AGRICULTURAL PRIVATIZATION - Čudan, Aleksandar L; Major, Gyöngyi; Ivanović, Zvonimir M (NBP. Nauka, bezbednost, policija, 2019)
Abstract: This scientific paper presents the knowledge and experiences related to the legalization of criminal profit with a view to agricultural ownership transformation in the Republic of Serbia. We define the concept, the standards aimed against money laundering and the real threats which create the possibility for this criminal offence in Serbia. The practical goal of the research is concerned with gaining further knowledge of the research topic, which would contribute to solving the current but also similar problems related to money laundering. In all countries transition privatization is a complex and painful process, and this refers to the agricultural sector particularly. This process is one of the fundamental factors of a market economy which must prevent legalization of contaminated money through legal flows. Parallel to this, organized crime expands the field of money laundering activities in the process of agricultural privatization. Starting from a previously defined problem the hypothesis this paper is based on is as follows: the risks of money laundering and new techniques for its integration are not possible to eliminate, but it is necessary to make efforts and undertake adequate measures to minimize them, particularly in the field of agriculture. The problem has become additionally complex due to the fact that at the beginning of 2016 the Privatization Agency ceased its operation according to the Law on Amendments to the Law on Privatization. The paper uses both general and specific scientific methods and procedures of logical conclusion, statistical, as well as positivist legal method. The manner of research includes the selection and application of scientific methods, the selection of data and the scope of research. The specific technique used to collect data in this paper includes case studies. Key words: privatization, money laundering, agriculture, crime